The Implementation of Wakalah Contract by Multifinance Companies in Indonesia - Rachmawaty Rachmawaty; Kartika Dian Pandaya; Alshamma Jamal Mohammed Al Azab (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2019)
The purpose of this paper is to discuss Wakalah contract which is one of the Islamic banking contracts. Therefore, our main study is the implementation of Wakalah in Indonesia. Wakalah in Indonesia has special reference which is Multifinance company (MFC). MFC is an entity of non-bank financial institution conducts business activities to finance goods or services.Therefore, this research is going to discuss how Wakalah is practiced in Indonesia, where Islamic banks appoint MFC as an agent to do service for end user “customer” on behalf of the bank. Consequently, the objective of this paper is to discuss the implementation of Wakalah with Mudharabah and Wakalah with Murabahah by MFC in Indonesia in terms of operation, the potential risks that might be occur and shariah issues in terms of ownership and fee. However, there are particular areas in terms of operation that MFC should improve, as well as, banks have to be aware of its operational way of conducting agreement so banks mitigate any kind of risks or negligence.